Interactions of dislocations in nanowires - Ng, Eddy Yan Wen. (2012)
In the engineering industry, nanocrystalline materials like nanowires has been rising topic for the recent decades. Nanocrystalline materials exhibit properties significantly different from their bulk materials due to the extremity in size. Though they are useful in a wide range of applications, defects within may either cause a drastic cut in their properties or have a compensation in stress. Disclinations are common defects in nanocrystalline materials processed via the severe plastic deformation technique. Depending on the strength of the disclination, dislocation walls may be emitted and these may in return partially relax the nanocrystalline material. An analysis on the interactions of dislocations in nanowires was conducted using closed-form analytical expressions for the strain energy within a nanograin. Using these expressions, it is found favourable dislocation spacings are to be as large as possible. In addition, the high disclination strengths correlate with large amounts of dislocations for the compensation of strain energy within the nanograin. Low disclination strengths are found to have low strain energies with low amount of dislocation.